Utilização de modelagens Uni e bidimensional para a propagação de onda de cheia proveniente de ruptura hipotética de barragem - estudo de caso: Barragem de Rio de Pedras - MG - Lucas Samuel Santos Brasil (2005)
The present study has the objective to evaluate the propagation of a flood wave caused by a dam failure using one and two-dimensional modeling approaches. Those approaches were applied to the case of the Rio de Pedras Dam, which is located in the rio das Velhas UpperBasin. The associated reservoir receives the contribution of a drainage area of 542 km². The total reservoir volume is about 6.0 hm³. The dam was made of concrete, type buttress, with 17 multiple arches. The total length of the crest is 122.00 m and the maximum height is 32.00 m.The flood, due to hypothetical dam breathing, was routed along 82 km of the rio das Velhas River, passing through the cities of Rio Acima, Raposos and Sabará, as well as two neighbourhoods of Nova Lima: Honório Bicalho and Santa Rita, in the Brazilian state of Minas Gerais. In order to simulate a dam failure event it is firstly necessary to determine the breach outflow hydrograph. The main characteristics to be obtained in the moment of the failure process are the form of the breach and its time formation. The routing of the flood wave caused by a dam failure involves phenomena of difficult mathematical characterization and with great variation of the hydraulic variables with time and space. Among the existent tools for the one-dimensional flood wave routing, the numerical model FLDWAV has been chosen. This model was developed by the National Weather Service and it is based on the solution of the complete Saint-Venant equations. The numerical model used for the wodimensional propagation of unsteady and gradually varied flow is the model FESWMS. This model was developed by U. S. Federal Highways Administration (FHWA) and it has been chosen because it is a hydrodynamic model that simulates two-dimensional discharge offluvial systems with complex topography. During the simulations carried out using the numerical model FLDWAV, a sensitivity study has been done to evaluate the influence of the peak discharge and the breach outflow hydrograph variation. The influences of the roughnesscoefficient and the number of cross sections, used to route the flood wave, was also verified.The numerical results were associated to the cartography of the area, with the intention of generating flood maps for rural and urban areas. The software IDRISI, developed by the George Perkins Marsh Institute at Clark University in Worcester, has been used to associate the data produced by the numerical simulation to the contour map of the study area. This model also allowed the delimitation of the flooded areas downstream of the dam for differentadopted scenarios.